Editor's Introduction: Paradigm Shift in Optic Neuropathy: Early Insights into Precise Etiological Differentiation - Indra Tri Mahayana, MD, PhD (Majalah Oftalmologi Indonesia, 2026)
Due of its heterogeneity in etiology, including inflammatory, vascular, and traumatic causes rather than as a singular condition and individual disease, the global prevalence of non-glaucomatous optic neuropathy (NGON) continues to be a challenging scientific difficulty.1,2,3 A retrospective study was performed at a tertiary eye‑care center in Yogyakarta, Indonesia, covering the period between January 2019 to December 2023 (4 years investigation period, including in the COVID-19 era). Read more >>>